Perception of Research Culture among Undergraduate Students in a Malaysian Public University - Sim, Edmund U. H. (Institute Press, Asia-Pacific International University, 2018)
Studies on research culture often focus on how administrators and academics inculcate this culture and what impact it has on undergraduates. Evidently, literature information on undergraduates’ perception of university research and publication agenda is lacking. Considering the fact that the campus community comprises largely of an undergraduate population and their activities, facts and conjectures alluding to research culture can be misleading without the views of undergraduate students. The study investigated the perception of research culture among undergraduate students in a Malaysian public university. The objectives of the study were to examine the students’ awareness of the research culture of the university, ranging from the research culture of the university as per the lecturers to the research reputation of the university. A survey was carried out using questionnaires incorporated within the e-learning platform (Morpheus) of a taught course on scientific communication. The analysis of questionnaire data from 56 students showed that undergraduates are more aware of research than publication matters. They do not think that good research correlates with better teaching. Local students are also indifferent to issues of university ranking. Our findings provide the basis for rethinking and deriving more accurate explanations of research culture appreciation in local public universities.